Integration of Criminology and Victimology Theories in the Protection of Human Rights in Islamic Criminal Law - Ashadi L. Diab; Annisa Ikke Rahmasari (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: The integration of criminology and victimology in the context of the protection of human rights (HAM) in Islamic criminal law is very necessary to be elaborated and clarified so that at the application level it does not give rise to debates and misunderstandings in society, and pays great attention to the protection of individual rights, including the rights of victims of crime. Objectives: This study analyzes the theories of criminology and victimology, as well as their relevance to the principles of human rights protection in Islamic criminal law. Criminology, as a study of crime and social deviance, as well as victimology that focuses on the study of victims of crime, provides a complementary perspective in looking at the dynamics of human rights violations, both from the perspective of perpetrators and victims as well as Islamic criminal law. Methods: This study explores how criminology and victimology approaches can contribute to a deeper understanding of the acts of crime in the social and moral context of Islam. This study assesses the potential for the integration of these two disciplines to strengthen efforts to protect human rights in the Islamic legal system. Result: Criminology and Victimology is a legal concept that discusses the rights of perpetrators and victims' rights. In this case, legal sanctions in Islamic crimes often receive the spotlight related to the punishment of the perpetrator of the crime and the protection of victims. is considered sadistic, cruel, and inhumane and contrary to human rights and human rights. Meanwhile, human rights and KAM in Islam are more holistic because they are to maintain the survival of human beings in the world. Conclusion: In this context, Islamic criminal law strongly upholds the right to life of human beings with full protection of human rights. So, it is somewhat unobjective if we only look at it from one side, namely the cruelty, without looking at the other side, namely the cruelty of criminal acts that have violated the honor of others (in the case of adultery); depriving others of their rights (in case of theft); and taking the lives of others (in the case of murder).